Risk Factors in Venous Thromboembolism - Martinelli, Ida (Thrombosis and Haemostasis, 2001)
Venous thromboembolism is a serious disorder because of its potential complications, such as pulmonary embolism and the post-thrombotic syndrome. Inherited determinants of venous thromboembolism are only in part known, but in the past decades considerable progress has been made in the understanding of risk factors for the disease and their clinical impact. In particular, the development of molecular biology techniques and the increasing interest in their application, allowed an identification of two causes of inherited thrombophilia, i.e., factor V Leiden and the prothrombin G20210A mutation. Their recent discovery provided a new approach for improving the knowledge of inherited thrombophilia. In contrast to deficiencies of the naturally occurring anticoagulant proteins antithrombin, protein C and protein S, these two mutations cannot be considered true genetic defects, since they are nucleotide substitutions resulting in a more efficient coagulation process. Since they are rather common in the general populations of Caucasian descent and are associated with a moderate increased risk of venous thromboembolism, the effect of the interaction between inherited and environmental risk factors for venous thromboembolism has become an even greater field of interest. Prevention of first events and recurrences of venous thromboembolism can be optimized only through a knowledge of the main risk factors, their effect, and their interaction with environmental factors.
Keywords: Thrombosis; coagulation; thrombophilia; gene-environment interaction